The evaluation of resolvent of generating operator for the linear systems with delay - Borisovitch, J.; Badojev, A. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Ю.Г. Борисович, А.Л. Бадоев. Оценка резольвенты производящего оператора для линейных систем с запаздываниемJ. Borisovičius, A. Badojevas. Tiesinių sistemų su vėlavimu generuojančio operatoriaus rezolventos įvertinimas